Rapid mass engagement ; driving continuous improvement through employee culture creation - Devine, Frank (Business consultant) (McGraw Hill, 2023)
"Dramatically improve business outcomes through a culture-change strategy that combines proven leadership, engagement, and continuous improvement methods Providing everything you need to boost individual, team, and organizational performance, Rapid Mass Engagement delivers a new, more effective approach to creating a solid corporate culture that fuels long-term business success"--